Gaussian Estimation of One-Factor Mean Reversion Processes - Freddy H. Marín Sánchez; J. Sebastian Palacio (Journal of Probability and Statistics)
We propose a new alternative method to estimate the parameters in one-factor mean reversion processes based on the maximum likelihood technique. This approach makes use of Euler-Maruyama scheme to approximate the continuous-time model and build a new process discretized. The closed formulas for the estimators are obtained. Using simulated data series, we compare the results obtained with the results published by other authors.